2022
DOI: 10.1093/toxsci/kfac116
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular administration of glyoxylate rescues swine from lethal cyanide poisoning and ameliorates the biochemical sequalae of cyanide intoxication

Abstract: Cyanide—a fast-acting poison—is easy to obtain given its widespread use in manufacturing industries. It is a high-threat chemical agent that poses a risk of occupational exposure in addition to being a terrorist agent. FDA-approved cyanide antidotes must be given intravenously, which is not practical in a mass casualty setting due to the time and skill required to obtain intravenous access. Glyoxylate is an endogenous metabolite that binds cyanide and reverses cyanide-induced redox imbalances independent of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…In regards to metabolite markers of therapeutic efficacy, previously, we demonstrated that cyanide poisoning induces substantially increased second-span citric acid cycle metabolites (26,46,59). Moreover, efficacious cyanide countermeasures restore normal levels of these metabolites.…”
Section: Metabolite Biomarkers Of Cyanide Toxicity and Therapeutic Ef...mentioning
confidence: 93%
See 4 more Smart Citations
“…In regards to metabolite markers of therapeutic efficacy, previously, we demonstrated that cyanide poisoning induces substantially increased second-span citric acid cycle metabolites (26,46,59). Moreover, efficacious cyanide countermeasures restore normal levels of these metabolites.…”
Section: Metabolite Biomarkers Of Cyanide Toxicity and Therapeutic Ef...mentioning
confidence: 93%
“…Pharmacokinetic studies demonstrated rapid glyoxylate absorption I both models. Finally, glyoxylate was well tolerated in rats at 1-and 5-days postadministration (26).…”
Section: Glyoxylate An Endogenous Metabolite Counteracts Cyanide Pois...mentioning
confidence: 93%
See 3 more Smart Citations